2005
DOI: 10.1007/s00330-005-2832-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined SPECT/CT imaging using 123I-IMT in the detection of recurrent or persistent head and neck cancer

Abstract: The aim of the study was to assess the clinical value of combined SPECT/CT imaging using L: -3-[123I]iodine-alpha-methyl tyrosine (IMT) for the differential diagnosis of recurrences in patients pre-treated for head and neck cancer. Thirty-four consecutive patients with biopsy-proven carcinomas, who had previously been treated by surgery and/or radio/chemotherapy, were examined at our clinic by IMT-SPECT using a dual-head system with integrated low-dose CT. SPECT results were correlated with histopathology, cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Although we are not aware of other reports assessing CUPS with brain SPECT and TRODAT-1 as the radiopharmaceutical, our results are in line with previous data that showed similar findings using iodine-123 labeled DAT radiotracers [5,[13][14][15][16][17][18]. Noteworthy, we did not expect that another DAT-marker as TRODAT-1 would be more useful in differentiating parkinsonian syndromes than the ones used in earlier studies.…”
Section: Discussionsupporting
confidence: 92%
“…Although we are not aware of other reports assessing CUPS with brain SPECT and TRODAT-1 as the radiopharmaceutical, our results are in line with previous data that showed similar findings using iodine-123 labeled DAT radiotracers [5,[13][14][15][16][17][18]. Noteworthy, we did not expect that another DAT-marker as TRODAT-1 would be more useful in differentiating parkinsonian syndromes than the ones used in earlier studies.…”
Section: Discussionsupporting
confidence: 92%
“…However, analogous to the FDG-PET, a high physiological IMT uptake in some head and neck regions represents an important limitation of the method, as noted by Dierickx et al [17]. In our previous investigation, we showed that the use of a hybrid gamma camera with integrated CT allows more precise localization of SPECT findings and allows their differentiation from physiological IMT accumulations [19]. The promising results of these studies encouraged us to evaluate the use of IMT-SPECT/low-dose CT in the diagnosis of recurrent head and neck cancer in a larger patient population.…”
Section: Discussionmentioning
confidence: 98%
“…Statistics were performed using SPSS v. 10 (SPSS Inc., Chicago, IL, USA). The calculation of the sensitivity, specificity and accuracy of IMT-SPECT in the detection of recurrent tumors was based on the results of the visual analysis of fused SPECT/low-dose CT, as our previous investigation showed that this was more accurate than the semiquantitative ROI analysis in the evaluation of recurrent head and neck tumors [19]. To calculate the sensitivity, specificity and accuracy of the method, the findings were compared to the final clinical diagnosis and classified as true-positive, true-negative, false-positive or false-negative.…”
Section: Discussionmentioning
confidence: 99%
“…In bone imaging, for example, combined SPECT/CT may improve diagnostic accuracy compared with SPECT only and help distinguish between osteomyelitis (Horger et al 2003), aseptic necrosis and metastatic disease. As with PET/CT, SPECT/CT has been shown to be beneficial in recurrent head and neck cancer imaged with 123I-IMT (Plotkin 2006). The accuracy of sentinel node mapping is improved by accurately localizing the affected nodes (Even-Sapir et al 2003).…”
Section: Diagnosis and Staging Of Diseasementioning
confidence: 99%